ALLOMORPHIC AND ISOMORPHIC FEATURES OF COGNITIVE SYNONYMS IN ENGLISH AND UZBEK LANGUAGES - Mahliyo Madiyarova Vaxid qizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Annotation: This article explores the cognitive synonyms in English and Uzbek, focusing on their allomorphic and isomorphic features. Isomorphic characteristics highlight shared semantic similarities and contextual applications, emphasizing how both languages utilize synonyms to enrich expression. In contrast, allomorphic features reveal cultural connotations, morphological differences, and idiomatic expressions unique to each language.